Peningkatan Kualitas dan Kuantitas Produksi Sepatu dengan Pemanfaatan Teknologi Tepat Guna - I Made Suparta; Tri Ratnawati; Suparno Suparno (JPM17: Jurnal Pengabdian Masyarakat, 2018)
There are 50 (twenty) households in Desa Kemasan that produce shoes such as Mr.Lukman Hakim in Kemasan Village and Mr. Putut Hardiyanto in Junwangi Village, where theyare gathered in the "Home of Shoe Industry" group. Business Partners are very hopeful toincrease their production and can make this household business become the main business.Some of the problems faced are business management that is still simple, marketing is stillin the form of orders and deposited around, the production process is done manually, andpackaging is less attractive. Based on these conditions, we offer a solution that is by providingappropriate technology in the form of shoe presses, plong machine and skilled small businessmanagement, marketing management and simple financial management.